Heat Transfer Enhancement of Diamond Rib Mounted in Periodic Merging Chambers of Micro Channel Heat Sink - Xin Lu; Lu Wang; Liangbi Wang; Yao Hu (Micromachines)
The heat transfer enhancement of diamond-shaped ribs mounted in the periodic merging chambers of microchannel (MC) heat sinks is investigated using a numerical method for Reynolds number in the region of 300–700. Compared to triangular, rectangular, and cylindrical ribs, diamond-shaped ribs achieve 3.59%, 13.24%, and 6.34% higher enhancement effects, respectively, under the same mass flow rate. Further analysis of geometric parameters (length, width, and height) and rib positioning reveals that a rib height of h/Hch = 0.8 provides optimal heat dissipation performance. For Re < 500, the optimal configuration is a rib length of l/Lmerg = 0.55 and a width of b/Wch = 0.8, while for 500 < Re < 700, it shifts to l/Lmerg = 0.36 and b/Wch = 1.6. For s/Lmerg, the smaller it is, the shorter the main flow separation time, thereby improving heat transfer efficiency.